A beta-sic ceramic and a method for making the same
Patent Information
- Application Number
- CN202410711530.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-06-03
AI Technical Summary
[0003]为克服β-SiC陶瓷的纯度、密度低的问题,本发明目的在于提供一种高纯度、高密度的β-SiC陶瓷及其制备方法
[0032]本发明将多孔陶瓷作为基体进行致密化处理,制备的β-SiC陶瓷具有高纯度、高密度的特点。
Abstract
Description
Technical Field
[0001] This patent relates to the field of SiC ceramic composite materials, specifically to a high-density, high-purity β-SiC ceramic and its preparation method. Background Technology
[0002] β-SiC ceramics possess excellent physical and chemical properties, such as high thermal conductivity, high hardness, and corrosion resistance, making them widely used in the semiconductor industry. β-SiC ceramics can be used to manufacture CVD silicon carbide components in etching equipment, including focusing rings, gas spray heads, trays, and edge rings. The sintering of β-SiC ceramics is based on an evaporation-condensation sintering mechanism, with no shrinkage during the firing process. Therefore, the prepared β-SiC ceramics have a porous structure and low bulk density, resulting in low strength and oxidation resistance, which severely limits their application in high-temperature oxidizing environments and makes them highly susceptible to structural failure, fragmentation, and deterioration. Therefore, the preparation of high-density, high-strength β-SiC ceramic materials is of great significance. Summary of the Invention
[0003] To overcome the problems of low purity and density of β-SiC ceramics, the present invention aims to provide a high-purity, high-density β-SiC ceramic and its preparation method.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing β-SiC ceramics, comprising the following steps:
[0006] Preparation of porous β-SiC ceramics;
[0007] A densification process for porous β-SiC ceramics was adopted. The impregnation slurry used in the impregnation-curing-pyrolysis process was prepared as follows: first, polycarbosilane and polysiloxane were weighed at a mass ratio of (85-95):(15-5) to prepare mixed slurry A; then, xylene solution was added to the mixed slurry to prepare impregnation slurry B, wherein the mass ratio of mixed slurry A to xylene solution was (75-65):(25-35).
[0008] The β-SiC ceramic is obtained after the impregnation-curing-pyrolysis process is carried out at least once.
[0009] Thus, porous β-SiC ceramics are first prepared and then densified using PIP (Polysiloxane Injection Process) as the matrix. Polycarbosilane can generate β-SiC through high-temperature pyrolysis, but this also produces impurities such as SiO2 and free carbon. A mixed slurry A is prepared using polycarbosilane and polysiloxane. The polysiloxane precursor in this slurry A undergoes a bond rearrangement reaction above 1000℃, separating into [SiO4] and [SiC4]. Then, the free carbon reacts with [SiO4] in a carbothermic reduction reaction to generate β-SiC. Simultaneously, because the introduced polysiloxane can uniformly encapsulate the polycarbosilane pyrolysis products at the molecular level and react in situ to form SiC, the free carbon content in the matrix can be effectively reduced, improving product purity.
[0010] In some embodiments, a method for preparing a β-SiC ceramic includes:
[0011] Preparation of porous β-SiC ceramics;
[0012] β-SiC ceramics are obtained by gradient densification treatment of porous β-SiC ceramics. The gradient densification treatment includes sequentially treating the porous β-SiC ceramics with first-stage impregnation-curing-pyrolysis and second-stage impregnation-curing-pyrolysis. The impregnation slurry used in the first-stage impregnation-curing-pyrolysis process is prepared as follows: first, polycarbosilane and polysiloxane are weighed at a mass ratio of (85-95):(15-5) to prepare mixed slurry A; then, xylene solution is added to the mixed slurry to prepare impregnation slurry B, wherein the mass ratio of mixed slurry A to xylene solution is (75-65):(25-35).
[0013] The preparation method for impregnation slurry C used in the second-stage impregnation-curing-pyrolysis process is as follows:
[0014] First, weigh polycarbosilane and polysiloxane in a mass ratio of (85-95):(15-5) to prepare mixed slurry A; then weigh xylene solution and add it to the mixed slurry to prepare impregnation slurry C. The mass ratio of mixed slurry A to xylene solution is (65-55):(35-45).
[0015] The first-stage impregnation-curing-pyrolysis and the second-stage impregnation-curing-pyrolysis are performed at least once each.
[0016] In some embodiments, the gradient densification process further includes a three-stage impregnation-curing-pyrolysis process;
[0017] The preparation method of impregnation slurry D used in the three-stage impregnation-curing-pyrolysis is as follows: First, weigh polycarbosilane and polysiloxane at a mass ratio of (85-95):(15-5) to prepare mixed slurry A; then weigh the polymer precursor vinyl-modified hydrogen polycarbosilane (KH-VHPCS) and add it to the mixed slurry to obtain impregnation slurry D. The mass ratio of mixed slurry A to polymer precursor vinyl-modified hydrogen polycarbosilane (KH-VHPCS) is (65-55):(35-45).
[0018] The first-stage impregnation-curing-pyrolysis, second-stage impregnation-curing-pyrolysis, and third-stage impregnation-curing-pyrolysis processes are performed at least once each.
[0019] In some embodiments, the prepared porous β-SiC ceramic has a bulk density of 2.35-2.43 g / cm³. 3 The open pore density is 14-16%.
[0020] In some embodiments, the impregnation slurry is heated to a temperature of 60-80°C at least before the impregnation-curing-pyrolysis process and / or the first-stage impregnation-curing-pyrolysis and / or the second-stage impregnation-curing-pyrolysis and / or the third-stage impregnation-curing-pyrolysis.
[0021] Thus, by changing the amount and type of solvent added, the viscosity of the impregnation slurry can be adjusted to prevent subsequent pyrolysis products from clogging the pores and thus preventing the slurry from entering the ceramic interior, affecting the density of the pyrolysis products. There is a negative correlation between the impregnation-curing-pyrolysis process: the solid content of the impregnation slurry and its impregnation ability are inversely related. Theoretically, a higher solid content in the slurry leads to a higher yield of β-SiC after high-temperature pyrolysis, but also a higher viscosity, resulting in poorer impregnation ability. During impregnation, the slurry cannot enter the pores, leaving less slurry in the β-SiC ceramic matrix after impregnation, resulting in a low weight gain rate after high-temperature pyrolysis. Conversely, a lower solid content in the slurry theoretically leads to a lower yield of β-SiC after high-temperature pyrolysis, but also a lower viscosity, resulting in better impregnation ability. During impregnation, the slurry enters the pores smoothly, leaving more slurry in the matrix after impregnation. However, due to the low solid content, the matrix weight gain rate after high-temperature pyrolysis is also not high. Therefore, mastering the balance point of the impregnation slurry is crucial for reducing the production cycle of the impregnation-curing-pyrolysis process. However, the balance point changes with the increase of the number of impregnation-curing-pyrolysis cycles. As the number of impregnation-curing-pyrolysis cycles increases, the porosity in the matrix decreases, the surface tension increases, and a lower viscosity impregnation slurry is required. Therefore, the three-stage impregnation-curing-pyrolysis process with a concentration gradient of impregnation slurry proposed in this invention balances the contradiction between the solid content and impregnation capacity of the impregnation slurry to the greatest extent, which helps to reduce the production cycle of the impregnation-curing-pyrolysis process.
[0022] In some embodiments, polycarbosilane and polysiloxane are weighed at a mass ratio of (85-95):(15-5) to prepare a mixed slurry. The prepared mixed slurry also includes pre-oxidized submicron-sized SiC particles with a size of 100-500 nm, added at a ratio of 5%-10% of the total mass of the mixed slurry.
[0023] Thus, by incorporating pre-oxidized submicron-sized SiC particles into a mixture of polycarbosilane and polysiloxane, β-SiC can be generated during pyrolysis through a carbothermic reduction reaction between the SiO2 on the particle surface and the free carbon in the polycarbosilane. This process consumes SiO2 and free carbon, further improving the purity of the product. Furthermore, the SiO2 on the surface of the SiC particles reacts with free carbon and SiC to generate CO and SiO, with higher surface tension indicating higher reactivity. The SiC particles blocking the pores in the matrix undergo a reaction with their surface SiO2 to generate gaseous products, resulting in a smaller particle size and weakened pore-sealing ability, thus providing a channel for the next impregnation slurry.
[0024] In some embodiments, the pyrolysis processes of first-stage impregnation-curing-pyrolysis, second-stage impregnation-curing-pyrolysis, and third-stage impregnation-curing-pyrolysis further include vacuum pyrolysis: the sample is pyrolyzed under vacuum, first heated to 600-700°C, held at 600-700°C for 1-2 hours, then heated to 1400-1700°C, held at 1400-1700°C for 1-3 hours, and finally cooled to room temperature.
[0025] Preferably, the pyrolysis regime is as follows: first, the temperature is increased to 600-700℃ at a rate of 1-3℃ / min, and held at 600-700℃ for 1-2 hours; then, the temperature is increased to 1400-1700℃ at a rate of 2-5℃ / min, and held at 1400-1700℃ for 1-3 hours; and then cooled to room temperature.
[0026] Thus, the pressure curing process solves the problem of slurry being discharged from the matrix pores due to pressure changes during the normal pressure curing process after the workpiece is removed from the pressure impregnation device, thereby increasing the SiC yield and reducing the production cycle of PIP.
[0027] β-SiC is a metastable phase at low temperatures. This invention employs a slow, segmented pyrolysis process, which effectively improves the pyrolysis efficiency of ceramics, reduces the phase transformation of β-SiC, and reduces the PIP cycle while improving product purity.
[0028] In some embodiments, after the gradient densification process, the method further includes: chemical vapor deposition sealing of the resulting β-SiC ceramic.
[0029] In some embodiments, chemical vapor infiltration is performed by introducing H2, Ar gas, and methyltrichlorosilane, wherein the H2 flow rate is 4-8 L / min, the Ar flow rate is 2-4 L / min, the methyltrichlorosilane (MTS) consumption is 400-600 g / h, and the deposition time is 10-15 h.
[0030] In some embodiments, the bulk density of the β-SiC ceramic prepared according to the present invention is approximately 2.7-3.0 g / cm³. 3 The apparent porosity is 0.5-4.5%, and the apparent density is 2.8-3.1 g / cm³. 3 .
[0031] The beneficial effects of this invention are as follows:
[0032] This invention uses porous ceramics as a matrix for densification treatment, and the prepared β-SiC ceramics have the characteristics of high purity and high density. Detailed Implementation
[0033] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0034] Example 1
[0035] (1) Preparation of porous β-SiC ceramics:
[0036] β-SiC powder and graphite powder were weighed at a mass ratio of 1:3% and mixed and ball-milled for 12 hours using anhydrous ethanol as the dispersion medium. The grinding balls were made of agate, and the ball-to-powder ratio was 2:1. The ball-milled mixture was dried in a rotary evaporator and then placed in an oven at 100℃ for 24 hours. After drying, it was removed and dry-pressed into shape. Under an Ar atmosphere with a pressure of 1 atm, the temperature was increased to 1900℃ at a heating rate of 8℃ / min and held at 1900℃ for 3 hours. Then, it was allowed to cool naturally to obtain porous β-SiC ceramic.
[0037] (2) First-stage impregnation-curing-pyrolysis:
[0038] a. Preparation of slurry: First, weigh polycarbosilane and polysiloxane at a mass ratio of 90:10 to prepare mixed slurry A; then weigh xylene solution and add it to mixed slurry A to prepare mixed slurry B. The mass ratio of mixed slurry A to xylene solution is 70:30.
[0039] b. Vacuum impregnation: After loading the porous β-SiC ceramic as the substrate into the tooling, place it into the impregnation tank, put the impregnation tank into the vacuum tank, start evacuation and heat the vacuum tank to stabilize the temperature at 70℃, stop evacuation when the pressure inside the vacuum tank is ≤1kPa, and maintain vacuum for 30min. Heat the mixed slurry in (2)a in an oil bath at 70℃. After the vacuum is maintained, suck the mixed slurry B into the impregnation tank through the pipe until the workpiece is immersed, remove the impregnation tank from the vacuum tank and wait for pressure impregnation.
[0040] Place the impregnation tank into the pressure impregnation container. After checking that the airtightness is good, evacuate to 150 Pa. Then, increase the temperature of the pressure impregnation container to 70°C at a rate of 2°C / min. Slowly introduce N2 until the internal pressure of the container reaches 4 MPa. Then, keep the temperature and pressure maintained for 6 hours before starting to raise the temperature to 170°C at a rate of 0.3°C / min. At this time, the internal pressure of the container is maintained at 4 MPa.
[0041] c. Pressure curing: After the internal temperature of the pressure impregnation container reaches the target temperature, the sample is kept under pressure for 6 hours to cure, and then cooled, depressurized, and removed.
[0042] d. Vacuum pyrolysis: The sample was pyrolyzed under vacuum. The pyrolysis regime was as follows: first, the temperature was increased to 650℃ at a rate of 2℃ / min, and held at 650℃ for 1.5h. Then, the temperature was increased to 1600℃ at a rate of 3℃ / min, and held at 1600℃ for 2h. Finally, the temperature was cooled to room temperature.
[0043] (3) Repeat step (2) 4 times.
[0044] Example 2
[0045] The difference from Example 1 is that, after step (3), the following is also included:
[0046] (4) Two-stage impregnation-curing-pyrolysis:
[0047] a. Preparation of slurry: First, weigh polycarbosilane and polysiloxane at a mass ratio of 90:10 to prepare mixed slurry A; then, weigh xylene solution and add it to mixed slurry A to prepare mixed slurry C, with a mass ratio of mixed slurry A to xylene solution of 60:40; then, weigh pre-oxidized submicron-sized SiC particles and add them to the mixed slurry at a ratio of 8% of the total mass of the mixed slurry.
[0048] b. Vacuum impregnation: After the first stage of impregnation-curing-pyrolysis process is completed, the β-SiC ceramic is loaded into the tooling and placed into the impregnation tank. The impregnation tank is then placed into the vacuum tank, and vacuuming is started and the vacuum tank is heated to stabilize the temperature at 70℃. Vacuuming is stopped when the pressure inside the vacuum tank is ≤1kPa, and the vacuum is maintained for 30min. The mixed slurry in (2)a is heated in an oil bath at 70℃. After the vacuum is maintained, the mixed slurry C is drawn into the impregnation tank through the pipeline until the workpiece is immersed. The impregnation tank is then removed from the vacuum tank and waited for pressure impregnation.
[0049] Place the impregnation tank into the pressure impregnation container. After checking that the airtightness is good, evacuate to 150 Pa. Then, increase the temperature of the pressure impregnation container to 70°C at a rate of 2°C / min. Slowly introduce N2 until the internal pressure of the container reaches 4 MPa. Then, keep the temperature and pressure maintained for 6 hours before starting to raise the temperature to 170°C at a rate of 0.3°C / min. At this time, the internal pressure of the container is maintained at 4 MPa.
[0050] c. Pressure curing: After the internal temperature of the pressure impregnation container reaches the target temperature, the sample is kept under pressure for 6 hours to cure, and then cooled, depressurized, and removed.
[0051] d. Vacuum pyrolysis: The sample was pyrolyzed under vacuum. The pyrolysis regime was as follows: first, the temperature was increased to 650℃ at a rate of 2℃ / min, and held at 650℃ for 1.5h. Then, the temperature was increased to 1600℃ at a rate of 3℃ / min, and held at 1600℃ for 2h. Finally, the temperature was cooled to room temperature.
[0052] (5) Repeat step (4) 4 times.
[0053] Example 3
[0054] The difference from Example 2 is that, after step (5), the following is also included:
[0055] (6) Three-stage impregnation-curing-pyrolysis:
[0056] a. Slurry preparation: First, weigh polycarbosilane and polysiloxane at a mass ratio of 90:10 to prepare mixed slurry A; then, weigh the polymer precursor vinyl-modified hydrogen polycarbosilane (KH-VHPCS) and add it to the mixed slurry to prepare mixed slurry D. The mass ratio of mixed slurry A to polymer precursor vinyl-modified hydrogen polycarbosilane (KH-VHPCS) is 60:40; then, weigh the pre-oxidized submicron-sized SiC particles and add them to the mixed slurry at a ratio of 8% of the total mass of the mixed slurry.
[0057] b. Vacuum impregnation: After the second stage impregnation-curing-pyrolysis process is completed, the β-SiC ceramic is loaded into the tooling and placed into the impregnation tank. The impregnation tank is then placed into the vacuum tank, and vacuuming is started and the vacuum tank is heated to stabilize the temperature at 70℃. Vacuuming is stopped when the pressure inside the vacuum tank is ≤1kPa, and the vacuum is maintained for 30min. The mixed slurry in (2)a is heated in an oil bath at 70℃. After the vacuum is maintained, the mixed slurry D is sucked into the impregnation tank through the pipeline until the workpiece is immersed. The impregnation tank is then removed from the vacuum tank and waited for pressure impregnation.
[0058] Place the impregnation tank into the pressure impregnation container. After checking that the airtightness is good, evacuate to 150 Pa. Then, increase the temperature of the pressure impregnation container to 70°C at a rate of 2°C / min. Slowly introduce N2 until the internal pressure of the container reaches 4 MPa. Then, keep the temperature and pressure maintained for 6 hours before starting to raise the temperature to 170°C at a rate of 0.3°C / min. At this time, the internal pressure of the container is maintained at 4 MPa.
[0059] c. Pressure curing: After the internal temperature of the pressure impregnation container reaches the target temperature, the sample is kept under pressure for 6 hours to cure, and then cooled, depressurized, and removed.
[0060] d. Vacuum pyrolysis: The sample was pyrolyzed under vacuum. The pyrolysis regime was as follows: first, the temperature was increased to 650℃ at a rate of 2℃ / min, and held at 650℃ for 1.5h. Then, the temperature was increased to 1600℃ at a rate of 3℃ / min, and held at 1600℃ for 2h. Finally, the temperature was cooled to room temperature.
[0061] (7) Repeat step (6) twice.
[0062] Example 4
[0063] The difference from Example 3 is that, after step (7), the following is also included:
[0064] (8) Chemical vapor infiltration sealing:
[0065] The β-SiC ceramic, after the third-stage impregnation-curing-pyrolysis process, was placed in a chemical vapor deposition chamber. The chamber was evacuated to below 1 kPa, heated to 1200 °C, and held at that temperature to obtain the target product.
[0066] Example 5
[0067] The difference from Example 4 is that:
[0068] In the mixed slurry A prepared in the first-stage impregnation-curing-pyrolysis, second-stage impregnation-curing-pyrolysis, and third-stage impregnation-curing-pyrolysis processes, the mass ratio of polycarbosilane to polysiloxane is 85:15; in mixed slurry B, the mass ratio of mixed slurry A to xylene solution is 75:25; in mixed slurry C, the mass ratio of mixed slurry A to xylene solution is 65:35; and in mixed slurry D, the mass ratio of mixed slurry A to the polymer precursor vinyl-modified hydrogen polycarbosilane (KH-VHPCS) is 65:35.
[0069] The pyrolysis regime was as follows: the sample was pyrolyzed under vacuum, first heated to 600℃ at a rate of 1℃ / min, held at 600℃ for 1h, then heated to 1400℃ at a rate of 2℃ / min, held at 1400℃ for 1h, and finally cooled to room temperature.
[0070] Example 6
[0071] The difference from Example 4 is that:
[0072] In the mixed slurry A prepared in the first-stage impregnation-curing-pyrolysis, second-stage impregnation-curing-pyrolysis, and third-stage impregnation-curing-pyrolysis processes, the mass ratio of polycarbosilane to polysiloxane is 95:5; in mixed slurry B, the mass ratio of mixed slurry A to xylene solution is 65:35; in mixed slurry C, the mass ratio of mixed slurry A to xylene solution is 55:45; and in mixed slurry D, the mass ratio of mixed slurry A to polymer precursor vinyl-modified hydrogen polycarbosilane (KH-VHPCS) is 55:45.
[0073] The pyrolysis regime was as follows: the sample was pyrolyzed under vacuum, first heated to 700℃ at a rate of 3℃ / min, held at 700℃ for 2h, then heated to 1700℃ at a rate of 5℃ / min, held at 1700℃ for 3h, and finally cooled to room temperature.
[0074] Example 7
[0075] The difference from Example 4 is that:
[0076] The preparation method of mixed slurry A is as follows: First, weigh polycarbosilane and polysiloxane at a mass ratio of 90:10, and then weigh pre-oxidized submicron-sized SiC particles with a size of 300nm at 8% of the total mass of polycarbosilane and polysiloxane.
[0077] Comparative Example 1
[0078] The difference compared to Example 4 is as follows:
[0079] The densification process was repeated 10 times, and there were no second-stage impregnation-curing-pyrolysis or third-stage impregnation-curing-pyrolysis.
[0080] Comparative Example 2
[0081] The difference compared to Example 4 is as follows:
[0082] The pyrolysis regime was as follows: the sample was pyrolyzed under vacuum, heated to 1300℃ at a rate of 5℃ / min, held at 1300℃ for 2 hours, and then cooled to room temperature.
[0083] test:
[0084] (1) Bulk density test:
[0085] The bulk density was tested using a bulk density meter.
[0086] (2) Apparent porosity test:
[0087] Apparent porosity was tested using a BET analyzer.
[0088] (3) Apparent density test:
[0089] The Archimedes displacement method was used to test the bulk density.
[0090] The test results are as follows:
[0091] Example 1 2.70 8.51 2.89 Example 2 2.87 4.26 3.01 Example 3 2.94 1.96 3.03 Example 4 2.94 1.93 3.05 Example 5 2.93 1.91 3.05 Example 6 2.94 1.92 3.04 Example 7 2.95 1.89 3.05 Comparative Example 1 2.76 7.63 2.94 Comparative Example 2 2.85 5.21 2.98
[0092] In Examples 1-3, the number of impregnation cycles was increased, and the concentration of the subsequent impregnation slurry was further modified, allowing more slurry to remain inside the matrix and pyrolyze to form β-SiC. Therefore, the bulk density, apparent porosity, and apparent density were all improved. In Example 4, CVD was added to further seal the surface of the obtained β-SiC, improving the apparent porosity and apparent density. Examples 5-6 changed the concentration of the impregnation slurry and the pyrolysis regime, all within the slurry viscosity range, so the changes were not significant compared to Example 4. In Example 7, pre-oxidized submicron-sized SiC particles were added to the mixed slurry A, which helped improve product purity and increase bulk density and apparent density. Simultaneously, the SiO2 on the particle surface reacted with free carbon and SiC to generate CO and SiO, resulting in a smaller particle size and weaker pore-sealing ability, providing a channel for the next impregnation slurry and further reducing apparent porosity.
[0093] Comparative Example 1 did not change the viscosity of the impregnation slurry. Due to surface tension, the slurry no longer penetrated into the pores after several impregnation cycles. Therefore, its bulk density and apparent density were both lower than those of Example 4, while its apparent porosity was higher. Comparative Example 2 did not undergo a segmented pyrolysis process. During the pyrolysis process, free C and other byproducts were generated, reducing the purity of β-SiC and causing the product performance to deteriorate compared to Example 4.
[0094] Although the present invention has been described in detail with reference to preferred embodiments, it is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing β-SiC ceramics, characterized in that, include: Preparation of porous β-SiC ceramics; The porous β-SiC ceramic is subjected to gradient densification treatment to obtain β-SiC ceramic. The gradient densification treatment includes sequentially treating the porous β-SiC ceramic with a first-stage impregnation-curing-pyrolysis process and a second-stage impregnation-curing-pyrolysis process. The impregnation slurry used in the first-stage impregnation-curing-pyrolysis process is prepared as follows: first, polycarbosilane and polysiloxane are weighed at a mass ratio of (85-95):(15-5) to prepare a mixed slurry A; then, xylene solution is weighed and added to the mixed slurry to obtain the impregnation slurry B, wherein the mass ratio of the mixed slurry A to the xylene solution is (75-65):(25-35). The preparation method for the impregnation slurry C used in the second-stage impregnation-curing-pyrolysis process is as follows: First, weigh polycarbosilane and polysiloxane at a mass ratio of (85-95):(15-5) to prepare mixed slurry A; then weigh xylene solution and add it to the mixed slurry to prepare impregnation slurry C. The mass ratio of mixed slurry A to xylene solution is (65-55):(35-45). The gradient densification process also includes a three-stage impregnation-curing-pyrolysis process; The impregnation slurry D used in the three-stage impregnation-curing-pyrolysis process is prepared as follows: First, polycarbosilane and polysiloxane are weighed at a mass ratio of (85-95):(15-5) to prepare mixed slurry A; then, the polymer precursor vinyl-modified hydrogen polycarbosilane is weighed and added to the mixed slurry to obtain impregnation slurry D. The mass ratio of mixed slurry A to polymer precursor vinyl-modified hydrogen polycarbosilane is (65-55):(35-45). The first-stage impregnation-curing-pyrolysis, the second-stage impregnation-curing-pyrolysis, and the third-stage impregnation-curing-pyrolysis are each performed at least once; In the first-stage impregnation-curing-pyrolysis, the second-stage impregnation-curing-pyrolysis, and the third-stage impregnation-curing-pyrolysis, the pyrolysis process parameters are as follows: The sample was pyrolyzed under vacuum. First, the temperature was raised to 600-700℃ and held at 600-700℃ for 1-2 hours. Then, the temperature was raised to 1400-1700℃ and held at 1400-1700℃ for 1-3 hours. Finally, the temperature was cooled to room temperature.
2. The method for preparing β-SiC ceramics as described in claim 1, characterized in that, The impregnation slurry is heated to a temperature of 60-80°C at least before the first-stage impregnation-curing-pyrolysis and / or the second-stage impregnation-curing-pyrolysis and / or the third-stage impregnation-curing-pyrolysis.
3. The method for preparing β-SiC ceramics as described in claim 2, characterized in that, The step of first weighing polycarbosilane and polysiloxane at a mass ratio of (85-95):(15-5) to prepare mixed slurry A further includes: the mixed slurry A also includes pre-oxidized submicron-sized SiC particles with a size of 100-500nm, and the addition ratio is 5%-10% of the total mass of the mixed slurry.
4. The method for preparing β-SiC ceramics as described in claim 3, characterized in that, The pyrolysis parameters are as follows: first, heat the temperature to 600-700℃ at a rate of 1-3℃ / min, hold at 600-700℃ for 1-2 hours, then heat the temperature to 1400-1700℃ at a rate of 2-5℃ / min, hold at 1400-1700℃ for 1-3 hours, and then cool to room temperature.
5. The method for preparing β-SiC ceramics as described in claim 1, characterized in that, The gradient compaction process further includes: Chemical vapor permeation sealing.
6. The method for preparing β-SiC ceramics as described in claim 5, wherein the chemical vapor infiltration sealing is characterized by introducing H2, Ar gas, and methyltrichlorosilane, wherein the H2 flow rate is 4-8 L / min, the Ar flow rate is 2-4 L / min, the methyltrichlorosilane consumption is 400-600 g / h, and the deposition time is 10-15 h.
7. A β-SiC ceramic, characterized in that, The β-SiC ceramic prepared by the method according to any one of claims 1-6 has a bulk density of 2.7-3.0 g / cm³. 3 The apparent porosity is 0.5-4.5%, and the apparent density is 2.8-3.1 g / cm³. 3 .
Citation Information
Patent Citations
Method for enhancing density of SiC / SiC ceramic matrix composite
CN105272262A
PIP (precursor infiltration and pyrolysis) rapid densification method of SiCf / SiC composite prefab
CN109485427A
Porous ceramics pore wall silicon carbide coating and its preparation method
CN1994974A
Preparation method of silicon carbide ceramics
KR1020110029026A
